FROM EDUCATIONAL POLICIES TO ACTUAL PRACTICES: YOUNG NEETS IN ROMANIA - Simona SAVA (National Centre for Policy and Evaluation in Education, 2020)
According to Eurostat data, the young NEETs (Not in education, employment or training) rate in Romania is one of the highest in Europe. It ranks 4th in Europe in 2019 (after Italy, Greece, and Slovenia) (Eurostat, 2020), with 11.5% for men, and 27.8% for women (while the EU average is 12.2% for men, and 20.8% for women). In addition, Romania has one of the highest rates of 'other NEETs', not registered by public employment agencies: only 4.8% were registered in 2018, and received the NEETs benefits (CE, 2018). Recent data show the low performance of Romania in monitoring the school to work transition of youths, in accessing the European funds to support young people entering the labor market, or for offering the Youth Guarantee (Beadle et al., 2020). Even so, Romania, like all other member states, cannot afford to lose the youth capital, while it faces sharp population ageing and outgoing migration. During the last decade, we saw emerging a strong know-how for understanding and addressing the NEETs issue. Reflecting on the research data from different reports and studies, from various findings in large scale H2020 research and innovation projects on NEETs, the paper elaborates on proactive or remedial integrative solutions for improving the situation of young NEETs in Romania, building up on the good practices in atracting NEETs, at national and European level, while using the theoretical framework of the governmentality studies applied to the youth field (Besley, 2010).